Produksi Dan Kualitas Telur Itik Lokal Lombok Untuk Bahan Telur Asin Yang Dipelihara Peternak Secara Intensif Di Lombok Tengah - Maskur Maskur; Sugeng Prasetyo; Lestari Lestari; Rahma Jan; Tapaul Rozi; Lalu Muhammad Kasip (Faculty of Animal Husbandry, University of Mataram, 2018)
A descriptive study using 30 female local Lombok ducks age ready to lay was carried out to know the local Lombok egg duck production and its quality raised intensively in Centre Lombok for making a salted egg. The observation was done in three months. Variable observed were eggs production (monthly production, egg weight, egg index), shell quality (texture, thickness, color), and internal egg quality (yolk index, yolk color, yolk and albumen weight ratio, egg spot). Data were analyzed by using simple statistic to get the mean and the deviation standard. The observation results were: monthly egg production in the first three months were 58,15 ± 10,98%; 60,25 ± 10,60%; 50,00 ± 15,73%; average egg weight and its index were 61,42 ± 2,73 gram and 0,74 ± 0,10. The shell surface was smooth and the thickness was 0,40 ± 0,09 mm. The shell color was greenish dark blue. The yolk index was 0,47, the yolk color varied between 10 and 14, the yolk albumen ratio was 1.04, and there was not an egg spot. The quality of the local Lombok egg ducks was good for making a salted egg.